2022
DOI: 10.3389/fnagi.2022.887581
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of time-compressed speech as a function of age in listeners with cochlear implants or normal hearing

Abstract: Speech recognition is diminished when a listener has an auditory temporal processing deficit. Such deficits occur in listeners over 65 years old with normal hearing (NH) and with age-related hearing loss, but their source is still unclear. These deficits may be especially apparent when speech occurs at a rapid rate and when a listener is mostly reliant on temporal information to recognize speech, such as when listening with a cochlear implant (CI) or to vocoded speech (a CI simulation). Assessment of the audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
(114 reference statements)
0
4
0
1
Order By: Relevance
“…1(A) and 1(B) ]. A 5% improvement in time-compressed speech recognition threshold would move trained older and middle-aged CI listeners closer to the performance of untrained younger CI listeners ( Tinnemore et al , 2022 ). Furthermore, a significant 6.3% improvement in speech recognition in noise was observed between pretest and posttest [Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1(A) and 1(B) ]. A 5% improvement in time-compressed speech recognition threshold would move trained older and middle-aged CI listeners closer to the performance of untrained younger CI listeners ( Tinnemore et al , 2022 ). Furthermore, a significant 6.3% improvement in speech recognition in noise was observed between pretest and posttest [Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Like older acoustic-hearing listeners, older CI listeners may experience greatly diminished speech recognition in challenging situations such as in the presence of background noise, competing speech, reverberation, and with time-compressed speech (e.g., Ji et al , 2013 ). Furthermore, the spectral degradation that occurs with a CI exacerbates the age-related deficits in time-compressed speech recognition ( Tinnemore et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). This creates a potential confound in experimental design because the ability to perceive vocoded stimuli decreases with age (Jaekel et al, 2018;Schvartz et al, 2008;Sheldon et al, 2008;Tinnemore et al, 2022). Some studies have suggested that the age effect could be a result of small differences in hearing thresholds (Shader et al, 2020), but there are alternative explanations.…”
Section: Barriers To Acoustic CI Simulationsmentioning
confidence: 99%
“…Além disso, a velocidade de fala irá influenciar na clareza da mensagem a ser transmitida. Nesse sentido, estudos demonstraram que independente do timbre vocal do locutor, ao falar com maior clareza e articulação o receptor da mensagem tende a ter melhoras significativas no diz respeito ao reconhecimento da fala (Picheny et al, 1989;Payton et al, 1994;Smiljanić and Bradlow, 2009) Pesquisas verificaram que a redução na velocidade da fala do locutor pode melhorar significativamente o reconhecimento da fala em deficientes auditivos e idosos (Gordon-Salant e Fitzgibbons, 1993;Schneider et al, 2005;Lessa and Costa, 2013;Winn e Teece, 2021;Tinnemore et al, 2022).…”
Section: Revisão De Literatura Quanto Aos Aspectos Temporais Que Impa...unclassified